SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT MENGGUNAKAN ALGORITMA C4.5 DAN METODE ANALYTICAL HIERARCHY PROCESS - Aleksander Bagas; Nina Setiyawati (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
PT. BPR Mekar Nugraha is one of the people's credit banks that has a high problem of bad credit. This is caused by many factors with one of the main factors namely the purpose of using credit is not in accordance with the credit application form. One way to solve the problem is by building a credit decision support system (SPK). In this research, SPK granting credit using C4.5 Algorithm and Analytical Hierarchy Process Method (AHP). The C4.5 is used as a calculation of customer data and AHP is used as a calculation of credit collateral. It is hoped that the SPK can provide alternative decisions and help credit analysts in the process of granting credit to customers. Of the 60 testing data used in the test, 71% of the test results are in accordance with the calculation of credit granting manually